1999
DOI: 10.1108/09604529910273201
|View full text |Cite
|
Sign up to set email alerts
|

A classified model for applying the theory of constraints to service organizations

Abstract: A classified model for applying the theory of constraints to service organizations Samia Siha Article information:To cite this document: Samia Siha, (1999),"A classified model for applying the theory of constraints to service organizations"If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 7 publications
1
36
0
Order By: Relevance
“…Thus, given the demonstrated effectiveness of theory of constraint's drum-buffer-rope (DBR) scheduling technique in the latter setting (Guide, 1996), there is reason to believe that DBR could be of benefit to better plan the operations in the hospital under study. The choice of DBR is also in agreement with Siha's (1999) suggestion that DBR can be useful in medical environments with an interaction of stochastic cure times, dependent events, and probabilistic care plans.…”
Section: Problem Characteristicssupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, given the demonstrated effectiveness of theory of constraint's drum-buffer-rope (DBR) scheduling technique in the latter setting (Guide, 1996), there is reason to believe that DBR could be of benefit to better plan the operations in the hospital under study. The choice of DBR is also in agreement with Siha's (1999) suggestion that DBR can be useful in medical environments with an interaction of stochastic cure times, dependent events, and probabilistic care plans.…”
Section: Problem Characteristicssupporting
confidence: 75%
“…Examples include airlines, trucking, hotels, and resorts and recreation. Siha (1999) defines the inventory for these organizations as the unused "service", such as a seat on a flight or space in a truck, and a room in a hotel or resort. The throughput is the money generated from selling the "service".…”
Section: Goal and Performance Measuresmentioning
confidence: 99%
“…Table 2 shows different implementation of TOC. Fenbert & Fleener, 2002;Wei et al, 2002√ Dettmer, 1995Ehie & Sheu, 2005;Moore & Scheinkopf, 1998;Nave, 2002;Raimona Zadry & Mohd Yusof, 2006;Siha, 1999;Stein, 1997√ Coman & Ronen, 2000Hilmola 2001√ Aryanezhad & Komijan, 2004Bhattacharya et al, 2008;Fawcett & Pearson, 1991;Fredendall & Lea 1997;Gupta et al, 2008;Lea & Min, 2003;Patterson, 1992;Souren et al, 2005;Umble et al, 2006√ Balakrishnan & Cheng, 2005√ Bhimani et al, 2002Cooper & Slagmulder, 1999;Fritzsch, 2011;Kee, 1995;Kirche et al, 2005;Ioannou & Papadoyiannis, 2004;Jones & Dugdale, 1998Louderback & Patterson, 1996;Schniederjans & Garvin, 1997;Spencer, 1994;Watson & Patti, 2008;Zimmerman & Yahya-Zadeh, 2011√ Bramorski et al, 1996√ Breen et al, 2002Motwani et al, 1996 √…”
Section: Resultsmentioning
confidence: 99%
“…The study also revealed that TOC measures (throughput, operating expense, and inventory) can be identified and measured to achieve global organization"s goal. Siha (1999) asserted that the recognition of organization constraints play an important role in achieving continuous improvement in service organizations. Techniques like drum-buffer-rope which are predominantly common in manufacturing arena can very well be applied in service sector to exploit system constraints and then subordinate resources to it.…”
Section: Literature Reviewmentioning
confidence: 99%